Hepatic hemangioma supplied by abnormal portal vein: A case report. Issue 4 (13th November 2019) - Ogawa, Masahiro; Matsumoto, Naoki; Kaneko, Masahiro; Kumagawa, Mariko; Watanabe, Yukinobu; Hirayama, Midori; Moriyama, Mitsuhiko; Higaki, Tokio; Takayama, Tadatoshi; Sugitani, Masahiko
Abstract: Hepatic hemangioma is the most common hepatic tumor with a prevalence of approximately 3%. It is typically supplied by the hepatic artery as evident from findings of abdominal angiography, contrast‐enhanced ultrasonography (CEUS), contrast‐enhanced computed tomography (CT), and contrast‐enhanced magnetic resonance imaging. However, few cases of hepatic hemangioma supplied by the portal vein have been reported. In this paper, we report a rare case of hepatic hemangioma supplied by the portal vein as shown on CEUS and CT arterioportography.